The Insights of Experienced Pharmacists Regarding the Iraqi health Insurance Program: A Qualitative Study(Conference Paper )# - Al-Jumaili, Ali Azeez; Sameer, Hayder Naji (Iraqi Journal of Pharmaceutical Sciences, 2023)
The aim of study was to explore pharmacist insights toward the impact of prospective implementation of the national health insurance program on patients, providers and Iraqi health system.This was a qualitative study including semi-structured face-to-face (mostly) interviews with experienced pharmacists. The interview guide included open-ended questions about the impact of the national health insurance program on patients and healthcare providers at three levels: quality of services, costs, and frequency of visits. Potential challenges were also discussed. Interviews were conducted in four provinces from March to May 2022. Thematic analysis was used to analyze the interview findings and generate themes and subthemes.The study recruited 21 pharmacists till the saturation point has been reached. Most of the participants were aware of the new health insurance law. Most participants believed that the program can enhance patient health and would increase the income of healthcare providers (HCPs) in the private sector. They also expected that patients would use private-sector services more frequently. Additionally, the implementation of the health insurance can improve the quality of healthcare services and reduce the financial burden regarding private sector fees. The potential challenges of the program include people's resistance to paying a monthly premium, difficulties in claims processing, potential delays in the reimbursement of HCPs, potential patient misuse of the insurance program, and the absence of an electronic system and database. There are not an adequate number of priced and tested medications.The health insurance program has several potential advantages, but at the same time it can face several technical challenges. The program should be well studied before implementing and it needs to be piloted at small scale before national implementation. The electronic system must be implemented by healthcare settings to facilitate transferring of the information/bills to the health authority. It is recommended to hire international team of experts to supervise the management this new system.